Working Memory Training and Speech in Noise Comprehension in Older Adults - Wayne, Rachel V.; Hamilton, Cheryl; Jones Huyck, Julia; Johnsrude, Ingrid S. (Frontiers in Aging Neuroscience, 2016)
Understanding speech in the presence of background sound can be challenging for older adults. Speech comprehension in noise appears to depend on working memory and executive-control processes (e.g., Heald & Nusbaum, 2014), and their augmentation through training may have rehabilitative potential for age-related hearing loss. We examined the efficacy of adaptive working-memory training (Cogmed; Klingberg, Forssberg & Westerberg, 2002) in 24 older adults, assessing generalization to other working-memory tasks (near-transfer) and to other cognitive domains (far-transfer) using a cognitive test battery, including the Reading Span test, sensitive to working memory (e.g., Daneman and Carpenter 1980). We also assessed far transfer to speech-in-noise performance, including a closed-set sentence task (Kidd, Best & Mason 2005). To examine the effect of cognitive training on benefit obtained from semantic context, we also assessed transfer to open-set sentences; half were semantically coherent (high-context) and half were semantically anomalous (low-context). Subjects completed 25 sessions (0.5-1 hour each; 5 sessions/week) of both adaptive working memory training and placebo training over 10 weeks in a crossover design. Subjects’ scores on the adaptive working-memory training tasks improved as a result of training. However, training did not transfer to other working memory tasks, nor to tasks recruiting other cognitive domains. We did not observe any training-related improvement in speech-in-noise performance. Measures of working memory correlated with the intelligibility of low-context, but not high-context, sentences, suggesting that sentence context may reduce the load on working memory. The Reading Span test significantly correlated only with a test of visual episodic memory, suggesting that the Reading Span test is not a pure-test of working memory, as is commonly assumed.